2020
DOI: 10.33000/mlspr.v3i1.468
|View full text |Cite
|
Sign up to set email alerts
|

Application of direct transcranial current as non-invasive therapy in eating disorders: an intervention proposal

Abstract: Palabras clave: Estimulación transcraneal con corriente directa (tDCS), anorexia nerviosa (AN), corteza prefrontal dorsolateral (dlPFC), tratamiento, patogenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…The EEG study by Grunwald et al [73] demonstrated hyperactivation in the RH of individuals with AN. Similarly, the positron emission tomography (PET) study conducted by Galusca et al focused on serotonin activity around 5-HT1A receptors in people with AN, revealing an increased number of serotonergic junctions, particularly in the fronto-temporal regions of the RH [74,75].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…The EEG study by Grunwald et al [73] demonstrated hyperactivation in the RH of individuals with AN. Similarly, the positron emission tomography (PET) study conducted by Galusca et al focused on serotonin activity around 5-HT1A receptors in people with AN, revealing an increased number of serotonergic junctions, particularly in the fronto-temporal regions of the RH [74,75].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…The pathogenesis of AN involves imbalances in serotonergic signaling in the ventral striatum, potentially related to the aversive aspects of the disorder [75,76]. Another theory proposes disruptions in reward pathways, as alterations in the dopamine system can affect reward circuitry, leading to anxiety and dysphoric moods [75,77].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 3 more Smart Citations